The cubital tunnel: a radiologic and histotopographic study. Issue 2 (10th June 2014) - Macchi, Veronica; Tiengo, Cesare; Porzionato, Andrea; Stecco, Carla; Sarasin, Gloria; Tubbs, Shane; Maffulli, Nicola; De Caro, Raffaele
Summary Entrapment of the ulnar nerve at the elbow is the second most common compression neuropathy in the upper limb. The present study evaluates the anatomy of the cubital tunnel. Eighteen upper limbs were analysed in unembalmed cadavers using ultrasound examination in all cases, dissection in nine cases, and microscopic study in nine cases. In all cases, thickening of the fascia at the level of the tunnel was found at dissection. From the microscopic point of view, the ulnar nerve is a multifascicular trunk (mean area of 6.0 ± 1.5 mm2). The roof of the cubital tunnel showed the presence of superimposed layers, corresponding to fascial, tendineous and muscular layers, giving rise to a tri‐laminar structure (mean thickness 523 ± 235 μm). This multilayered tissue was hyperechoic (mean thickness 0.9 ± 0.3 mm) on ultrasound imaging. The roof of the cubital tunnel is elastic, formed by a myofascial trilaminar retinaculum. The pathological fusion of these three layers reduces gliding of the ulnar nerve during movements of the elbow joint. This may play a role in producing the symptoms typical of cubital tunnel syndrome. Independent from the surgical technique, decompression should span the ulnar nerve from the triceps brachii muscle to the flexor carpi ulnaris fascia.